(untitled) (RuMoRes, 2013)
This article casts light on the growth of the zombie film production in Latin America, taking into account issues such as affordable digital video technology and new means of circulating independent film production. This overview starts with notes on foundational elements of the zombie motif in American and British film production. The beginnings of the Latin American zombie cinema in the 1960s, as well as its rise in the wake of international horror cinema, are also focused by this survey, which addresses particularly Mexican, Argentine and Brazilian films. In all these Latin American filmographies, zombie cinema presents regional traits and trends that deserve detailed analyses.